Peripartum Isolated Cortical Vein Thrombosis in a Mother with Postdural Puncture Headache Treated with an Epidural Blood Patch - Etienne Laverse; Sarah Cader; Rajith de Silva; Sanjiv Chawda; Satish Kapoor; Olaleye Thompson (Case Reports in Medicine)
A 32-year-old woman presented with low pressure headache 3 days after delivery of her baby. An assessment of postdural puncture headache was made. This was initially treated with analgesia, caffeine, and fluids for the presumed cerebrospinal fluid (CSF) leak. The woman was readmitted two days after her hospital discharge with generalised seizures. A brain scan showed features of intracranial hypotension, and she was treated for CSF leak using an epidural blood patch. Her symptoms worsened and three days later, she developed a left homonymous quadrantanopia. An MRI scan confirmed a right parietal haematoma with evidence of isolated cortical vein thrombosis (ICVT).